Spinal ganglion cyst of lumbar posterior longitudinal ligament causing lumbar stenosis with neurogenic claudication: Case report - Giovanni Carlo La Delfa, MD; Daniele Carmelo Caltabiano, MD; Alfio Cannella, MD; Clara Di Lorenzo, MD; Antonio Ragusa, MD; Pietro Trombatore, MD; Simone Cottonaro, MD; Gianluca Galvano, MD (Radiology Case Reports)
This case report describes a 24-year-old male with a spinal ganglion cyst originating from the posterior longitudinal ligament (PLL) of the lumbar spine, an uncommon site for ganglion cysts. The patient exhibited symptoms of neurogenic claudication (NC), initially thought to be spinal stenosis, however MRI showed a cystic lesion instead, compressing L2-L3 nerve roots. The case illustrates the importance of differential diagnoses in spinal cystic lesions and highlights surgical excision as an effective treatment for symptomatic relief.